A transfer molding process using particulate composite material and virtual testing - Kumar S.; Pande S.S.; Kumawat B.C. (My University, 2025)
There have been several attempts to find a material alternative for wood with suitability of ease for manufacturing. The paper presents development of a transfer molding process for making different producfs using a special class of composite material toreplace wood. The process uses saturated polyester based resin with French chalk powder as filler for fabrica tion. A stool mold in several pieces has been prepared by reinforcing chopped glass fibre mat in unsaturated polyester resin by hand lay -up process. Flowability and temperature experiments have been performed in order to identify the working process parameters and transfer molding process has been used to reproduce the product from mold. Mechanical properties of the proposed composite material have also been calculated virtually using Hypermesh 5.1 software. Results indicate that the proposed material is safe and it is suitable for different applications.